Differential Pulley Release in Trigger Finger: A Prospective, Randomized Clinical Trial. (March 2023) - Wu, Robin T.; Walker, Marc E.; Peck, Connor J.; Liu, Yuen-Jong; Hetzler, Peter; Le, Nicole K.; Smetona, John; Thomson, J. Grant
Background: The palmar aponeurosis or "A0 pulley" may play a role in trigger finger pathology. This study assesses the involvement of the A0 pulley in patients receiving trigger finger release. Methods: This single-surgeon, prospective, randomized clinical trial was conducted among consenting patients with symptomatic trigger finger. Intraoperative coin toss was used to randomize initial release of either the A0 or A1 pulley. Following release, active flexion and extension of the affected digit were examined. The remaining pulley was then released in sequence, and clinical trigger status was recorded. Results: Thirty fingers from 24 patients were released; 17 fingers received A0 release first, and 13 received A1 release. Following initial A0 release, 8 fingers (47%) demonstrated complete resolution of symptoms, 4 (24%) demonstrated improvement but incomplete resolution of triggering, and 5 (29.4%) demonstrated no improvement. Following initial A1 release, 6 fingers (46%) demonstrated complete resolution, 3 (23%) demonstrated improvement but incomplete resolution of triggering, and 4 (31%) demonstrated no improvement. All patients demonstrated complete resolution after surgical release of both sites. Neither initial A1 release nor initial A0 release was statistically associated with complete, incomplete, or failed symptom resolution. Conclusions: These data implicate the A0 pulley as the primary cause of 31% to 47% of trigger fingers in our study. Although larger trials are needed to validate these results, our study suggests that release of both A0 and A1 pulleys may offer greater symptom resolution than release of the A1 pulley alone.